Some aspects of long term co-operative agricultural finance : a study of two areas in Gujarat - Jodha, N. S.; Bhat, M. L. (The Centre, 1971)
On the contribution of the Gujarat State Co-operative Land Development Bank to assist farmers in mechanisation for increased production.